PERAN PANGLIMA LAOT DALAM MEWUJUDKAN KEBERLANJUTAN WISATA BAHARI DI PROVINSI ACEH - Taufik Taufik; Lailatussaadah Lailatussaadah (Lembaga penelitian dan Pengembangan Masyarakat (LPPM) IAIN Kediri, 2020)
AbstractTourism has become one of the sectors contributing to the country's economic growth. In order for tourism to be sustainable, community participation is needed in its management,Â one of them is the role of customary institutions. This qualitative study aims to categorizing the types of tourism in Aceh and analyze the roles and obstacles of